2022
DOI: 10.1111/joes.12499
|View full text |Cite
|
Sign up to set email alerts
|

A prolonged period of low interest rates in Europe: Unintended consequences

Abstract: We examine the potential adverse effects of a prolonged period of low interest rates on financial stability from multiple perspectives. First, we provide a unique comparison of natural rates of interest estimated using two approaches—with and without financial factors—for six large European countries inside and outside the euro area. Second, we provide a comprehensive review of the empirical literature, allowing us to identify and categorize financial vulnerabilities, which may be created and fueled by low int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…Although the interest rate was not statistically significant determinant of insurers" financial stability, it is necessary to state that the analysed period was connected with a low interest rate in the Czech Republic. Malovaná et al (2020) suggested that low interest rates may undermine the solvency of insurance companies and or ESRB (2015) added that the scenario of a prolonged low-interest rate environment in conjunction with a drop-in asset prices is considered to be one of the most destabilizing events for European life insurers and the real economy as well. However, since 2020 in the Czech Republic, the interest rate has increase, the supervisory authorities as well as the management of insurers could focus the attention on the insurance stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the interest rate was not statistically significant determinant of insurers" financial stability, it is necessary to state that the analysed period was connected with a low interest rate in the Czech Republic. Malovaná et al (2020) suggested that low interest rates may undermine the solvency of insurance companies and or ESRB (2015) added that the scenario of a prolonged low-interest rate environment in conjunction with a drop-in asset prices is considered to be one of the most destabilizing events for European life insurers and the real economy as well. However, since 2020 in the Czech Republic, the interest rate has increase, the supervisory authorities as well as the management of insurers could focus the attention on the insurance stability.…”
Section: Discussionmentioning
confidence: 99%
“…However, since 2020 in the Czech Republic, the interest rate has increase, the supervisory authorities as well as the management of insurers could focus the attention on the insurance stability. As Malovaná et al (2020) pointed, if a period of low interest rates ends with a sudden rise in rates, insurance policyholders may withdraw their funds ahead of maturity (surrender). This will become a source of liquidity vulnerability for insurance companies (CGFS 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Statistically, this can be driven by the fact that the period of low interest rates coincides with substantially increased macroprudential policy activity (Alam et al., 2019). Record low interest rates have depressed bank profitability and may have encouraged risk taking and hence increase the probability of default (for a literature review, see Malovaná et al., 2022). The associated risks were aimed to be contained by increased engagement of macroprudential policy.…”
Section: Drivers Of Heterogeneitymentioning
confidence: 99%
“…What is particularly interesting is the effect of the low interest rates seen before 2008 on the relationship between credit risk materialization and structural risks. Based on the emerging literature on the topic, we assume that low interest rates may amplify the negative impact of structural risks on credit risk (Bikker & Vervliet 2018, Malovana et al 2020, ESRB 2021.…”
Section: Considering the Thresholds Of Structural Risksmentioning
confidence: 99%